Circular And Digital Economies Under Climate Change: Development and Governance Through the History of Economic Thought - Kamalakumari, K. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
Climate change has fundamentally challenged the legal and economic foundations of development models that prioritise continuous growth and expanding consumption. In response, contemporary policy and regulatory discourse increasingly promotes the circular economy and digital transformation as pathways toward climate-resilient and sustainable development. However, whether these approaches represent a genuine shift away from growth-centric paradigms or merely reconfigure them through technology remains an open question. This paper examines this tension through the lens of the history of economic thought, offering a normative framework relevant to climate change law and governance. Revisiting classical political economy, the paper shows that early thinkers such as Adam Smith, Thomas Malthus, David Ricardo, and John Stuart Mill viewed economic activity as embedded within moral obligations and natural limits. These concerns were progressively displaced by neoclassical growth theories that abstracted the economy from ecological constraints and treated environmental harm as an externality. Marx’s critique of capital accumulation further exposed the structural drivers of environmental degradation, while twentiethcentury ecological economics reasserted biophysical limits and intergenerational responsibility. Against this intellectual background, the paper critically evaluates the contemporary circular and digital economy agendas. It argues that the circular economy holds meaningful potential to support climate-compatible development when anchored in binding legal mechanisms such as lifecycle responsibility, resource accountability, and absolute environmental thresholds. By contrast, the digital economy presents a more ambivalent trajectory: while enabling environmental monitoring, transparency, and regulatory enforcement, it simultaneously intensifies energy use, extractive pressures, and new forms of inequality. The paper concludes that climate change law must move beyond efficiency-based and technologically optimistic responses toward historically informed governance frameworks that integrate ecological limits, distributive justice, and accountability. Such an approach reframes development not as unlimited expansion, but as a legally regulated process of equitable transformation within planetary boundaries.
Keywords: Climate change law; Circular economy; Digital economy; Sustainable development; Environmental governance; History of economic thought